Masjid Sebagai Sentra Dakwah Wasathiyah (Studi Tentang Aktivitas Dakwah Masjid Agung Nurul Falah Kabupaten Paser) - Amirullah, Amirullah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study is motivated by the mosque, which is considered